Neurocognition and subjective experience following acute doses of the synthetic cannabinoid JWH‐018: a phase 1, placebo‐controlled, pilot study - Theunissen, Eef L (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: Synthetic cannabinoids (often sold as Spice or K2) have become a very popular alternative to cannabis due to their easy access and portrayed safety. Controlled studies on the behavioural effects of synthetic cannabinoids are currently lacking, which hampers risk assessments of these compounds. EXPERIMENTAL APPROACH: This is a first attempt to assess the influence of a synthetic cannabinoid, JWH‐018, on neurocognition and subjective experience in humans after controlled administration. JWH‐018, 2 and 3 mg, was administered to six healthy cannabis‐experienced volunteers in a placebo‐controlled, cross‐over study following an escalating dosing schedule. Participants were monitored for 12 h after drug administration, and several neurocognitive measures and subjective questionnaires were taken. KEY RESULTS: Serum concentrations of JWH‐018 were highest after the 2 mg dose but generally low after administration of both doses. Both doses of JWH‐018 were well tolerated, and no serious side effects were reported. Participants reported feeling more ‘high’ at 1 and 2 h after administration, particularly after the 2 mg dose. Behavioural impairments also emerged despite the low serum concentrations of JWH‐018. The low dose of JWH‐018 impaired performance on the tracking, divided attention and stop signal task. CONCLUSION AND IMPLICATIONS: JWH‐018 dosing in the present study resulted in drug concentrations that were generally low and not fully representative of common use. Yet initial impairments of neurocognitive function and subjective feelings of high did emerge despite low levels of JWH‐018 in serum. Higher doses are needed to obtain a more representative risk profile of JWH‐018.